BIAYA REVEGETASI GAMBUT BERDASARKAN KARAKTERISTIK SPESIFIK LAHAN GAMBUT - Rina Muhaya; Asysyifa Asysyifa (Lambung Mangkurat University-Indonesia, 2021)
Peat revegetation is an effort to reduce the rate of areas reduction and the decreasing of storing capability of carbon and to restore the ecological function of peatlands. The purpose of this study was to analyze the cost components of peatland revegetation activities and to analyze the cost of each peat revegetation activity component. The research location taked place in 2 (two) villages, Haur Gading District, HSU Regency, South Kalimantan. The components of revegetation costs were grouped into: transportation costs, tools and mateials, payment and other costs. Data obtained from surveys and field observations and interviews. The data analysis used were a tabulation matrix and a comparison of each cost component for revegetation activities from the 2 compared villages. The total cost of Village A peatland revegetation activities is 10,851,018/ha. The characteristics of the community in Village A are very participatory and willing to cooperate with outside parties so that revegetation activities in this Village run well. The very high value of mutual cooperation and the desire to put common interests first became the basis for their actions. Village B revegetation activity costs Rp.12,117,883.00/ha. The very large costs involved in the procurement of seedlings due to the addition of 3,500 seedlings/21ha as replacements for dead, damaged or lost seedlings. The difference in the cost of revegetation activities is IDR 1,266,865/ha. This shows that a high level of participation and cooperation is able to reduce the cost of revegetation of peatlands.